Isometria submáxima envolvendo grandes grupos musculares induz hipotensão pós-exercício e melhora o estado redox em adultos hipertensos estágio 1 - Olher, Rafael dos Reis Vieira (2019)
Hypertension is known to be one of the major risk factors for cardiovascular diseases in the world. On the other hand, recent scientific evidence suggests that isometric strength exercise (ISE) could be part of antihypertensive treatment. However, little is known regarding acute cardiovascular responses involving large muscle mass and the possible mechanisms involved in post-isometric exercise hypotension (PIEH) in hypertensive adults. The Nitric oxide (NO-) and oxidative stress (OE) may be important elements involved in the pathophysiology of hypertension. The aim of this study was to investigate the hemodynamic, oxidative stress and plasma concentrations of nitric oxide responses to a submaximal isometric exercise involving large muscle mass in leg press 45º (LP45) and bench press (BP) equipment. Fourteen hypertensive (HT–7-♂, 7-♀)age: 35.9 ± 8.1 years, height: 1.73 ± 0.10 m, body mass: 78.0 ± 15.8 kg, systolic blood pressure (SBP): 128.89 ± 11.95, diastolic blood pressure (DBP) 82.96 ± 5.08 and 10 normotensive (NT–5-♂, 5-♀): age: 41.1 ± 9.4 years, height: 1.71 ± 0.12 m, body mass: 82.3 ± 22.4 kg, SBP: 115 ± 1.65, DBP: 71.75 ± 6.51 individuals were submitted to two experimental sessions in the LP45 and BP, being: i) control session (without exercise) and ii) experimental session (SEI) with 8 sets x 1-min contraction at 30% maximal voluntary isometric contraction (MVIC) with 2-min rest interval, the sessions were carried out in randomized order. Blood Pressure (BP) was measured rest and during 60-min post-exercise. Blood samples were collected at rest, immediately after the session and 60-min post-exercise. The NO- was obtained through the Griess reaction method. The OS parameters were analyzed using commercial kits. A repeated-measures ANOVA with Bonferroni’s post-hoc was used to analyze all dependent variables. A significant decrease post-exercise in systolic BP was observed only for HT at 45-min (p=0.003, Δ%=4.44%) and 60-min (p=0.018, Δ%=5.58%) in relation to rest. No significant differences were obtained for NT. With respect to NO- both groups increased the Bioavailability immediately post-exercise. Regarding OS parameters, the analysis of thiobarbituric acid reactive substances (TBARS) presented a significant reduction in relation to the rest at 60-min post-isometric exercise in both groups. Whereas the catalase activity increased in both groups immediately post-exercise, remaining increased after 60-minpost exercise. We can conclude that submaximal isometric exercise with large muscle mass involved promotes an increase in pro-oxidant activity leading to an increase in NO-bioavailability, an increase in antioxidant activity and consequently decrease in pressure levels in hypertensive adults.